Differential Short-Term Repeated Forearm Hyperaemic Reactivity in Coronary Artery Disease Patients Compared to Healthy Low Risk Participants. (12th November 2012) - Bacon, Simon L.; Meloche, Bernard; Lavoie, Kim L.; Arsenault, André
Abstract : The hyperaemic response of the forearm is a widely used technique to assess the vascular reactivity. Little is known about the short-term reproducibility and the possible exhaustion of this response in normal or diseased states. As such, the current study was conducted to assess this phenomenon using a unique nuclear medicine- (NM-) based technique. 19 patients with coronary artery disease (CAD) undergoing NM exercise stress tests and 15 low risk (LR) participants completed 2 reactive hyperaemia tests, using a SPECT-based technique, separated by 15 min. Analyses revealed that CAD patients had lower hyperaemic responses than LR participants (P < .001 ), and that there was a significant group × time interaction (P < .005 ), such that LR participants showed a larger decrease in the reactivity (5.2 ± 0.4 to3.6 ± 0.4 ) than the CAD patients (2.9 ± 0.3 to2.6 ± 0.3 ). These results suggest that there is a variability, due to disease states, in the reproducibility of the hypaeremic reactivity. This needs to be taken into account in short-term repeated measure studies.